PH OF THE TOPICAL DRUG VEHICLE: SELECTING AN OPTIMUM VALUE AND ROLE OF THE BUFFER SYSTEM - A. S. Dukhanin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The following three groups of factors must be taken into consideration for selecting an optimum pH value of a topical drug: pharmaceutical, pharmacological and compatibility factors. To ensure a stable pH value, the drug vehicle comprises different buffer systems: single component and two-component ones. The optimum conditions for selecting and maintaining the vehicle pH were examined by the example of glucocorticosteroid-based topical drugs.